Investigating the high yield extraction of pectin from Crissampelos Pareira L. Vat. Hirsute planted in Vietnam - Nguyen, Van Toan; Xuan Quyen, Duong (International Journal of Scientific Research and Management (IJSRM), 2022)
The study on the most suitable extracting conditions of pectin from Crissampelos pareira L. Var. Hirsute was thoroughly and successfully investigated. It was found that the most suitable conditions for the extraction of pectin from C pareira were at temperature of 90°C; pH of solution of 1.5; and the extraction time of 60 minutes. The average yield of pectin was of 15.58%. it is worth noting that the mentioned extracting conditions showed a highly significant effect (p